2021
DOI: 10.53097/jmv.10035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Trendelenburg position during prone ventilation in fifteen COVID-19 patients. Observational study

Abstract: Background Prone position ventilation has shown to improve oxygenation and mortality in severe ARDS. The data of prone position ventilation during severe ARDS secondary to COVID-19 have shown similar benefit in oxygenation and mortality. Usually, patient placed in prone position are placed flat or in reverse Trendelenburg positioning to decrease risk of aspiration and abdominal girth compressing the chest. To date, no studies are available to compare the effects of positioning the bed in different angles durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…29,30 A recent observational study by our group in COVID-19 proned patients showed that when placing the patient in the trendelenburg position, the tidal volume and the respiratory compliance markedly improved. 31 Regarding the perceived benefits of the prone position for the COVID-19 patients, our results again showed no statistically significant agreement with a majority of those surveyed (45%) who claimed the maneuver is beneficial in 25%-50% of cases but wide variety of perception from the extremes of no benefits or highly beneficial in more than 75% of the cases. Those results reflect the current literature of unknown mortality benefits for COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 77%
“…29,30 A recent observational study by our group in COVID-19 proned patients showed that when placing the patient in the trendelenburg position, the tidal volume and the respiratory compliance markedly improved. 31 Regarding the perceived benefits of the prone position for the COVID-19 patients, our results again showed no statistically significant agreement with a majority of those surveyed (45%) who claimed the maneuver is beneficial in 25%-50% of cases but wide variety of perception from the extremes of no benefits or highly beneficial in more than 75% of the cases. Those results reflect the current literature of unknown mortality benefits for COVID-19 patients.…”
Section: Discussioncontrasting
confidence: 77%
“…The Trendelenberg position during the proning position is more optimal than the flat position with the head turned to the right or left because the Trendelenberg position increases tidal volume and lung compliance. (Kodamanchili et al, 2022;Su et al, 2021). Image 3.…”
Section: Image 1 Precise Size Of Proning Mattressmentioning
confidence: 99%